Strategies of Sanity and Survival: Religious Responses to Natural Disasters in the Middle Ages - Hanska, Jussi (Studia Fennica Historica, 2002)
It is an unusual book in many respects. It is a specific study based on original and in most cases unedited sources, but it can also be read as a general introduction. It crosses boundaries between different fields of learning and traditionally accepted time periods of history. Even if it is essentially a book on medieval man, it stretches far beyond the middle ages as conventionally understood. The final chapter traces the slow disappearance of the medieval mentality until the early nineteenth century.